Wunderlich Syndrome Managed with Angiomyolipoma Embolization – Renal Artery Anatomic Variant Augmenting Safe and Nephron-Sparing Intervention - Tripathy, Tara Prasad; Alagappan, Alamelu; Patel, Ranjan Kumar; Behera, Srikant Kumar; Panda, Sandip Kumar; Naik, Suprava (Acta medica Lituanica, 2024)
Background: Wunderlich syndrome is an uncommon entity characterized by spontaneous, nontraumatic renal bleeding into the subcapsular and perirenal regions. The most frequent benign tumor, angiomyolipoma, is the most common cause of Wunderlich syndrome.Case presentation: We report a case of Wunderlich syndrome in angiomyolipoma. Intratumoral pseudoaneurysm arising from feeders of an accessory renal artery supplying the lower pole of the kidney was selectively embolized. Rarely does a sporadic renal angiomyolipoma develop a giant pseudoaneurysm.Conclusion: Transarterial embolization is imperative to control the bleeding or as a preventative measure to reduce the risk of intralesional pseudoaneurysm rupture. When vascular interventional facilities are unavailable, surgery may be necessary.